2008
DOI: 10.1016/j.ijheatfluidflow.2007.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence modeling of the Von Kármán flow: Viscous and inertial stirrings

Abstract: The present work considers the turbulent Von Kármán flow generated by two counter-rotating smooth flat (viscous stirring) or bladed (inertial stirring) disks.Numerical predictions based on one-point statistical modeling using a low Reynolds number second-order full stress transport closure (RSM model) are compared to velocity measurements performed at CEA (Commissariatà l'Énergie Atomique, France). The main and significant novelty of this paper is the use of a drag force in the momentum equations to reproduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…The predictions of the RSM model have already been widely validated in various rotating disk configurations: turbulent Batchelor flows in a rotor-stator cavity (regime IV of [1]) with or without an imposed axial throughflow [2,3], with heat transfer effects [25], turbulent Stewartson flows in an open cavity with throughflow [2,3], and turbulent Von Kármán flow between counterrotating disks equipped or not with straight blades [26]. Nevertheless, to show the performances of the present model, the results of the RSM code are compared to both velocity measurements performed at IRPHE by a two-component laser Doppler anemometer and numerical predictions using the k-ε model of Launder and Sharma [27] for Re = 10 6 , G = 0.036, and several values of the flowrate coefficient C w .…”
Section: Validation Of the Rsm Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The predictions of the RSM model have already been widely validated in various rotating disk configurations: turbulent Batchelor flows in a rotor-stator cavity (regime IV of [1]) with or without an imposed axial throughflow [2,3], with heat transfer effects [25], turbulent Stewartson flows in an open cavity with throughflow [2,3], and turbulent Von Kármán flow between counterrotating disks equipped or not with straight blades [26]. Nevertheless, to show the performances of the present model, the results of the RSM code are compared to both velocity measurements performed at IRPHE by a two-component laser Doppler anemometer and numerical predictions using the k-ε model of Launder and Sharma [27] for Re = 10 6 , G = 0.036, and several values of the flowrate coefficient C w .…”
Section: Validation Of the Rsm Modelmentioning
confidence: 99%
“…Some discrepancies remain along the stator in the case of very strong inward throughflows because of the different prerotation levels used in the model and measured in the experiment [11]. Considering also the previous validations in various interdisk cavities [2,3,25,26], the RSM model can now be used with confidence for a parametric study of turbulent rotor-stator flows.…”
Section: Validation Of the Rsm Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the work proposed here has the importance of treating a study that was not done before; it is the influence of the rotating speed ratio of the rotating cylinders on the distribution of the turbulence in the annular space and especially the relation between this parameter and the level of turbulence in this kind of flows. The same study has done by Poncet et al [17] but this study has done for rotating discs and not for rotating cylinders as we propose in our present study. The study of Iacovides and Toumpanakis [18], in which four models of turbulence are examined, proves that the model of transport of the tensions of Reynolds is the suitable level of closing to study such complex flows.…”
Section: Introduction Former Workmentioning
confidence: 61%
“…The axis of z corresponds to the axis of rotation. We note Γ the rotating speed ratio of the interior cylinder by the external one and we vary Γ from [17] has showed that the phenomena of unsteady problems and instability start have to appear only for one very high rotation corresponding to a Reynolds number of rotation higher than 10 6 . 5 2 10 …”
Section: Geometry Of the Flowmentioning
confidence: 99%